Malignant peripheral nerve sheath tumor of adrenal gland with heterologus osseous differentiation in a case of Von Recklinghausen's disease - Manas R Baisakh; Nachiketa Mohapatra; Samiran D Adhikary; Debasis Routray (Wolters Kluwer Medknow Publications, 2014)
Malignant peripheral nerve sheath tumor (MPNST) of the adrenal gland is extremely rare. Most of them occur in association with neurofibromatosis, ganglioneuroma or as part of a composite tumor such as pheochromocytoma. Only seven cases of MPNST of the adrenal gland have been reported in the literature till date. Discriminating this entity from other soft tissue sarcomas and gastrointestinal stromal tumor of the adrenal gland has important diagnostic and therapeutic implications. Moreover, the tumor size and pattern of expression for certain immunohistochemical markers may serve as independent predictors of aggressiveness. Herein we present a 24-years-old male with features of Von Recklinghausen's disease who presented with large left adrenal gland malignant peripheral nerve sheath tumor.